Resistance of (Aegilops tauschii × Secale cereale) × Triticosecale Hybrids to Leaf Rust (Puccinia triticina) Determined on the Macroscopic and Microscopic Level - Majka, Maciej; Serfling, Albrecht; Czembor, Paweł; Ślusarkiewicz-Jarzina, Aurelia; Kwiatek, Michał Tomasz; Ordon, Frank; Wiśniewska, Halina (Frontiers in Plant Science, 2018)
Leaf rust caused by Puccinia triticina Eriks belongs to the most important fungal pathogens of wheat (Triticum aestivum L.) and triticale (× Triticosecale). Effective resistance to leaf rust is both, cost-effective and environmentally safe. Many wild Aegilops species carry unknown resistances against fungal diseases and are characterized by a high genetic variability. The main goal of this work was to examine the resistance of (Ae. tauschii × S. cereale) × Triticosecale hybrids to leaf rust in inoculation tests with different races of P. triticina. Hybrid plants were selected for the presence of 2D chromosome/s in the triticale background using fluorescence and genomic in situ hybridization. The presence of leaf rust resistance genes was confirmed with closely linked molecular markers i.e. Xgdm35 and Xgwm296. 14 genotypes of BC2F4 - BC2F6 hybrid plants with the monosomic addition of chromosome 2D (M2DA) were analyzed together with eight control lines. Resistance was determined at the macroscopic and microscopic level at the seedling and adult plant stage (flag leaf). In general, results revealed limited resistance of hybrid plants at the seedling stage, followed by an increase of the resistance level at later stages of plant development. This indicates respective hybrid plants may exhibit APR resistance conferred by Lr22a introgressed from Ae. tauschii. On the basis of the macroscopic and microscopic analysis, this kind of resistance turned out to be additive and race-specific. We selected four monosomic 2D addition triticale genotypes highly resistant to P. triticina infection at the two main stages of plant development. From the selected genotypes, we obtained 26 doubled haploid lines among which two lines with doubled additional chromosomes 2D of Ae. tauschii can be used for further breeding to increase leaf rust resistance of cultivated triticale.